THE PROTECTION OF ADULTS IN THE EUROPEAN UNION (EU and comparative law issues and challenges series (ECLIC), 2019)
A far-reaching freedom of movement of persons in the European Union imposes the EU legislator’s obligation to create a legal framework for regulating an increasing number of aspects arising from cross-border movements. The current legal arrangement of these aspects is to a great extent related to the protection of family life and the rights of children. However, strong migrations have also affected people who are considered vulnerable in terms of their disability or age. Travelling that has become easier, medical treatments available abroad, a desire to live in more attractive or more affordable countries in retirement, and a change of lifestyle in general, have made the elderly move more frequent during the past decade. Cross-border proceedings arising from the movement of older people have become more common before the courts of Member States. It is necessary to ensure that protective measures directed at vulnerable adults, which have been imposed by the authorities of one Member State, have their effect in another Member State. This situation implies the adoption of the rules of private international law that will regulate the issues as to authorities of which Member States are responsible for adopting protective measures, which law is applicable to such measures, under which conditions these measures are to be recognized in that other Member State and the cooperation of the competent authorities. These issues are regulated by the Convention on the International Protection of Adults, adopted within the framework of the Hague Conference on Private International Law. While, on the one hand, the European Union is a Contracting State to the UN Convention on the Rights of Persons with Disabilities and is obliged to take its standards into account in its policies and legislation, on the other hand, very few Member States are Contracting Parties to the Convention on the International Protection of Adults. At EU level, there are currently only recommendations for the regulation of private international law aspects related to mobility of vulnerable adult persons, which also include the adoption of a special regulation that will govern these issues. However, among the existing recommendations, the winning attitude is the one that calls for Member States to ratify the Convention on the International Protection of Adults. Starting with the hypothesis that the European Union does not provide any effective legal framework for the protection of vulnerable adults in cross-border cases, this paper will examine whether there is room for the introduction of enhanced mechanisms for the protection of adults at EU level and make proposals accordingly.